The Processing and Marketing of Seeds from the Amazon City of Porto Velho,RO - Rivero,Sidney (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2013)
This article aims to show through an epistemological perspective that the sustainability conscious actions implemented in the Amazon rainforest region of the municipality of Porto Velho-RO, have not been created to prevent economic development or the survival of small investors who work with the raw material from the forest. In this region, there arises a proposal for community organization with the help of the Government agencies mentioned that aims at supplementing the lack of technical knowledge for the correct handling of material taken from the forest, with the possibility of managerial and technical maturity by the organized community, looking into making their businesses more effective, at the expense of amateurism. Based also on social difficulties concerning unemployment in the country, the environmental entrepreneur activity can be a consistent alternative to many who cannot find employment or insertion into the disputed work market, as well as, possibly becoming a complementary income for those who already work.